Investigation of FimH adhesin among Enterobacter spp. isolates and their role in biofilm formation - Mohammad S. Abdul azzaq, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
One hundred five urine samples were collected from patients with cystitis and subjected to uriscan Cybow10 dipstick to investigate presence of leukocyte in urine (pyuria) using leukocyte esterase test (LET) and using of nitrite test (NT) to detect bacteriuria. Only samples who gave positive result for both leukocyte esterase test and nitrite test would be then subjected to culture. Twenty four Enterobacter isolates were recoverd from urine samples (9 isolates were E. cloacae (EC) and 15 isolates were E. aerogenes (EA). All DNA samples extracted from bacterial isolates were conducted for PCR to investigate presence of fimH gene among isolates. The result revealed that 18/24(75%) of isolates were positive to fimH gene (6 isolates among E. cloacae and 12 isolates among E. aerogenes).Phenotypic detection of biofilm formation was performed using Tissue culture plate (TCP) assay and the results demonstrate that, 17/24(70.8%) were biofilm former among which 7(29.2%) biofilm former belong to E. cloacae and 10(41.6%) belong to E. aerogenes. The results display significant positive correlation between biofilm formation and FimH adhesin expression in which fimH gene was present in 16/17(94.1%) of biofilm former isolates. Our results conclude the importance of FimH adhesin in establishment of biofilm and magnitude of biofilm formation in cystitis via antibiotics resistance and ascending infections.